Analisis Kepuasan Pengguna Menggunakan Technology Acceptance Model Pada Aplikasi Dana - Musdalifah Musdalifah; Elvin Leander Hadisaputro (Journal of Computer System and Informatics (JoSYC), 2022)
DANA is an application that provides convenience in digital transactions in Indonesia. Human lifestyle has begun to shift significantly, where everything is required to be done quickly, easily, and practically. One form of practicality that exists in the community is the rise of online systems. Currently, DANA is an e-wallet payment that is still relatively new in the community. Therefore, this DANA application is still in the development stage so this research needs to be done to attract millennials. This study aims to determine user satisfaction with the application of funds for employees of Telkom sharpening. This study uses the Technology Acceptance Model (TAM) method with five variables, namely Perceived Usefulness (X1), Perceived Ease Of Use (X2), Attitude Toward Using (X3), Behavior Intention To Use (X4) and Actual Use (Y). It is known that the research results Perceived Usefulness with a percentage value of 82.66%, perceived easy of use with a percentage of 80%, Attitude Toward Using with a percentage value of 80.53%, Behavioral Intention to Use with a percentage value of 80% and actual use with a percentage value of 82 ,4% with the category Strongly Agree. From the results of perceived satisfaction, it can be stated that Telkom Penajam Office Employees are very satisfied with using the Dana application.